Decomposing local fiscal multipliers: Evidence from Japan - Taisuke Kameda; Ryoichi Namba; Takayuki Tsuruga (Osaka University, Institute of Social and Economic Research (ISER), 2019)
Recent studies on fiscal policy use cross-sectional data and estimate local fiscal multipliers along with spillovers. This paper estimates local fiscal multipliers with spillovers using Japanese prefectural data comparable with the national accounts. We estimate the local fiscal multiplier on output to be 1.7 at the regional level. The regional fiscal multiplier consists of the prefecturespeci fic components and a component common across prefectures within the same region, which we interpret as the region-wide effect. Converting the latter component into the spillover, we find that the spillover is positive and small in size. We decompose the regional fiscal multiplier on output into multipliers on expenditure components. The regional fiscal multiplier on absorption exceeds 2.0 because of the crowding-in effect on consumption and investment. Moreover, we find that the spillover to absorption is considerable in contrast to the spillover to output.
Keywords: E62; H30; R50; 330; Fiscal stimulus; spillover; geographic cross-sectional scal multiplier